Pengaruh Brand Community Engagement dan Brand Image Terhadap Brand Loyalty Emina Cosmetics di Lingkungan Mahasiswa Universitas Sumatera Utara - Yabes Abi, Wilmer Nicholas; Theresa, Fannysia; Lumumba Siahaan, Peron; Aulia Rifki, Muhammad; Gea, Willem (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
This research aims to analyze the influence of brand community engagement and brand image on brand loyalty to Emina Cosmetics among students at the University of North Sumatra. A quantitative approach was used with purposive sampling technique, involving respondents who meet specific criteria, such as being members of the Emina Girl Gang. Data was processed using SmartPLS 3.0 to test validity, reliability and relationships between variables. The research results show that brand community engagement has a positive and significant effect on brand loyalty with a T-statistic value of 4.536 (p < 0.05). Interaction in brand communities like Emina Girl Gang creates a strong sense of community and social identity, which drives loyalty through emotional connection. Meanwhile, brand image has a more dominant influence on brand loyalty with a T-statistic value of 5.776 (p < 0.05). A positive image of the Emina brand, such as high product quality and suitability to student lifestyles, strengthens consumer trust and loyalty. The R-square value shows that the independent variables in this study explain 53.7% of the variance in brand loyalty. Thus, marketing strategies based on strengthening brand communities and creating a positive brand image have proven effective in increasing customer loyalty, especially in the student segment.